2015
DOI: 10.1016/j.clon.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Genetic Biomarkers into Predictive Models of Normal Tissue Toxicity

Abstract: There is considerable variation in the level of toxicity patients experience for a given dose of radiotherapy, which is associated with differences in underlying individual normal tissue radiosensitivity. A number of syndromes have a large effect on clinical radiosensitivity, but these are rare. Among non-syndromic patients, variation is less extreme, but equivalent to a ±20% variation in dose. Thus, if individual normal tissue radiosensitivity could be measured, it should be possible to optimise schedules for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 79 publications
0
43
0
Order By: Relevance
“…It is well known that, even when patients are treated with the same curative dose, normal tissue toxicity shows variability between patients, indicating inter-individual differences in the intrinsic radiosensitivity1345. The mechanisms influencing intrinsic radiosensitivity still remain unclear and many factors may contribute to it, but it has been suggested that up to 80% of this variability could have a genetic basis3678.…”
mentioning
confidence: 99%
“…It is well known that, even when patients are treated with the same curative dose, normal tissue toxicity shows variability between patients, indicating inter-individual differences in the intrinsic radiosensitivity1345. The mechanisms influencing intrinsic radiosensitivity still remain unclear and many factors may contribute to it, but it has been suggested that up to 80% of this variability could have a genetic basis3678.…”
mentioning
confidence: 99%
“…Measurements of radiosensitivity using only cell based assays have faced uncontrolled experimental variability [23]. Here we show an association between T4EM lymphocytes radiosensitivity and three SNPs within the TRAIL/TNFSF10- gene.…”
Section: Discussionmentioning
confidence: 75%
“…With the availability of stereotactic radiotherapy and increasingly proton therapy, defined patient groups at risk for toxicity based on their genetic profile and not only on dosimetric parameters (11,12) may be considered for these modalities.…”
Section: Interventionsmentioning
confidence: 99%